ANALISA PERESAPAN AIR PADA LAPANGAN SEPAK BOLA DI STADION GELORA SRIWIJAYA PALEMBANG (Universitas Muhammadiyah Palembang, 2022)
The soccer field is one of the most important facilities in this stadium to support soccer. The occurrence of puddles during the match must be avoided for the smooth running of a match. In planning for water infiltration on the soccer field at the Gelora Sriwijaya Stadium, Palembang, a subsurface drainage system is used. The purpose of this study was to determine the appropriate infiltration system during the rainy season with plans for 2, 5, and 10 years. Hydrological analysis was calculated by analyzing the frequency of rain data using three distribution methods, namely normal distribution, log normal, and log Pearson III. Next, the best distribution method was selected based on the ch-square and Smirnov Kolmogrov fit test. The design of the water infiltration system on the soccer field at the Gelora Sriwijaya Stadium in Palembang is a sub-surface drainage (subdrain) which is analyzed from several calculation parameters, namely pipe dimensions, channel depth, and distance between drain pipes. Furthermore, it is compared to the rain intensity (I) at the time of concentration (tc) which occurs in the 2nd return period; 5; and 10 years to determine the occurrence of inundation in the field according to the analysis of water infiltration planning. The known data are technical specifications, while the analysis of calculations at the time of the planned rain return is not known. From this study, the calculation results showed that the diameter of the subsurface drain pipe of 4 inches did not occur inundation, so there was no need for normalization.